A Clinical-Epidemiological Study on Beta-Blocker Poisonings Based on the Type of Drug Overdose - Nastaran Eizadi-Mood; Mahtab Adib; Arman Otroshi; Gholamali Dorooshi; Rokhsareh Meamar (Journal of Toxicology)
Background. Beta‐blockers carry a high risk of potentially causing fatal poisoning if overdosed. We aimed to assess the clinical and epidemiological characteristics of patients with beta-blocker poisoning. Methods. Patients were categorized based on the type of drug poisoning into propranolol, other beta-blockers, and the combination of beta-blocker groups, respectively. Demographic data, drug toxicity, and clinical, laboratory, and treatment information of different groups were compared. Results. During the study period, 5086 poisoned patients were hospitalized, of whom 255 (5.1%) had beta-blocker poisoning. Most patients were women (80.8%), married (50.6%), with a history of psychiatric disorders (36.5%), previous suicide attempts (34.6%), and intentional type of exposure (95.3%). The mean ± SD age of the patients was 28.94 ± 11.08 years. Propranolol toxicity was the most common among different beta-blockers (84.4%). There was a significant difference in age, occupation, education level, and history of psychiatric diseases with respect to the type of beta-blocker poisoning (P<0.05). We observed changes in the consciousness level and need for endotracheal intubation only in the third group (combination of beta-blockers). Only 1 (0.4%) patient had a fatal outcome in toxicity with the combination of beta-blockers. Conclusion. Beta-blocker poisoning is not common in our poisoning referral center. Propranolol toxicity was most common among different beta-blockers. Although symptoms are not different among defined beta‐blocker groups, more severe symptoms are observed in the combination of the beta-blocker group. Only one patient had a fatal outcome in the toxicity with the combination of the beta-blocker group. Therefore, poisoning circumstances have to investigate thoroughly to screen coexposure with combined drugs.